Marangoni convection within thermosolute and absorptive aqueous LiBr solution. (1st June 2022) - Pranowo,; Makarim, Dio Afinanda; Suami, Akira; Wijayanta, Agung Tri; Kobayashi, Nobusuke; Itaya, Yoshinori
Highlights: Marangoni convection during steam absorption into LiBr solution is investigated. RBF meshless method for solving Marangoni convection has not been reported. The Marangoni number has a range of 0 ≤ Ma ≤ 1000. For low Prandtl number values, convection flow occurs at the interface. Increasing Marangoni number can strengthen the convection flow magnitude. Abstract: The Marangoni convection during steam absorption into an aqueous lithium bromide (LiBr) solution is investigated numerically. In order to obtain a better understanding of the physical mechanism of thermal convection in the solution, the influence of surface tension on the absorbing solution is explored. For this purpose, this paper proposes the radial basis function (RBF) meshless method for numerical simulation of thermosolutal convection and vapor absorption in aqueous LiBr solution problems. The spatial terms of the governing equation are discretized using the RBF meshless method. The fractional step method is used for solving the continuity equations and momentum equations. The coupled energy and species equations are solved iteratively. The semi-algebraic system is solved using an implicit backward Euler scheme to maintain stability. The no-slip boundary conditions are imposed on solid wall surface. The surface tension gradient and the energy balance due the phase change are imposed on the interface of vapor and solution interface. The thermosolutal convection problem is presented to examine the accuracy of proposed method. An analytical solution is also presented for validating the vapor absorption problem results for zero Marangoni number ( Ma ). The Marangoni number used has a range of 0 ≤ Ma ≤ 1000. The increase in Marangoni number for low Prandtl number values does not significantly affect heat and mass transfer. However, increasing Ma for LiBr solution has a significant effect. It is also found that the velocity of convection flow can be improved by adding a solid object to the interface.